Prevalence of methicillin-sensitive, methicillin-resistant Staphylococcus aureus, and extended-spectrum beta-lactamase-producing Escherichia coli in newborns: a cross-sectional study. (17th November 2022) - Heigl, Katharina; Zamfir, Mihai; Adler, Alexandra C.; Dammeyer, Antchen; Schomacher, Lasse; Karlin, Barbara; Franitza, Manuela; Hörmansdorfer, Stefan; Tuschak, Christian; Valenza, Giuseppe; Ochmann, Uta; Herr, Caroline; et al.
Abstract: Background: The prevalence of antimicrobial-resistant bacteria and methicillin-sensitive Staphylococcus aureus (MSSA) in healthy newborns and the role of maternal transmission are scarcely discussed. Objectives: The objective of this study was to evaluate the prevalence of MSSA, MRSA, and ESBL among healthy newborns. Additionally, mother-to-newborn transmission rates were investigated as well as antibiotic susceptibility of MSSA, MRSA, and ESBL isolates. Methods: Swabs of 658 newborns and their mothers were collected to investigate the presence of MSSA, MRSA, and ESBL. Swabs were taken from the nose and umbilicus immediately after birth. Additional swabs were taken from the nose, perianal area, and umbilicus 3 days after birth. Samples were screened and further characterized using culture and molecular methods. Results: Prevalence of MSSA, MRSA, and ESBL colonization was 10.9, 0.5, and 2.6%, respectively. There was no association between the colonization status of the newborn and infections at any time point. Mother-to-newborn transmission rates (confirmed by PFGE) were 53.6% for MSSA/MRSA and 100% for ESBL. Maternal carriage of MSSA, MRSA, or ESBL was a risk factor for colonization of the newborn. Some isolates were resistant to the antibiotics recommended for therapy, including clindamycin and daptomycin for MSSA/MRSA isolates and ertapenem, fosfomycin, and tigecyclin for ESBL isolates. Conclusion: No association between infections and the newborns' colonization status could be detected. Maternal colonization played an important role in newborn colonization, but not every case of colonization could be explained by mother-to-newborn transmission. General screening of pregnant women and healthy newborns in the absence of other risk factors is not necessary. To prevent the possibility of transmission in the healthcare setting, professionals, pregnant women, parents, hospital visitors, and obstetricians should receive regular training on appropriate hygiene measures. With regard to the emergence of resistance to recommended antibiotics, an antibiogram should be conducted before treating MSSA/MRSA/ESBL infections to ensure the efficacy of the antibiotics.